Social impacts of mining : a Western Australian community case study - Petrova, Svetla Lyubomirova (Curtin University, 2012)
Social impacts of mining is not a new area of study. The intensive resource extraction over the last ten years, together with the societal challenges occurring at a global scale, and the progress of the sustainability agenda, are changing the way mining impacts on local communities. Understanding the social implications of mining operations at the local community level appears to be a challenging research exercise that resembles a complex puzzle.The study presented in this thesis seeks to explore the complexities and drivers generating social impacts of mining at a local community level and how this relates to community’s long-term development. The concept of social sustainability is the primarily focus used to examine and interpret the consequences from contemporary mining operations. Studying the rural community of Boddington in south-west Australia, the research links the concepts of social impacts and social sustainability. It reflects on the qualitative changes occurring in the social landscape and analyses the role of mining for long-term community development by examining its contribution against the social implications it evokes.The findings of this inquiry demonstrate the complex nature of the social impacts caused by mining operations. It identifies three new phenomena impacting the social sustainability prospects of the community, namely the appropriation of human resources, transiency and dependency culture. The case study unveils the inextricable links between the drivers that generate impacts and brings forward the importance of analysing and exploring the dynamic interactions between the various social indicators in order to understand how mining affects local communities.